ANALISIS PENGARUH PERUBAHAN SENTRASI DOSIS DAN JARAK BLADDER TERHADAP DISTRIBUSI DOSIS PADA PERENCANAAN BRACHYTHERAPY KANKER SERVIKS - Rinarto Subroto; Evi Setiawati; Suwardi Suwardi (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
The research has been done about the analysis of the change dose sentration and bladder distance’s effect toward dose distribution in brachytherapy planning of cervical cancer. The purpose of this research is to describing dose distribution which is appropriate with criteria, to evidance dose reduction because raising bladder distance from point A, and to achieve how long the bladder distance’s from point A which is can produce the dose distribution criteria appropriate.The methods of this research is measuring bladder distance from point A in lateral projections of radiographs, doing brachytherapy planning which is using early dose sentration at the point A. The sample who is have not ideal dose disribution doing brachytherapy planning with dose sentration at point bladder. The dose distribution which is producted from the change of dose sentration has analysis to know how about brachytherapy planning succes percentage. To evidance about dose reduction because raising of bladder distance’s, has done with making distance and bladder dose’s relation graph.The results of this research is: changing of dose sentration can increasing cervical brachytherapy planing successed about 46%, raising mean distance about 1,57 mm can reduce bladder mean dose about 5,65%, inverse square law still valid for brachytherapy planning case’s although can’t used to determine how much dose at the bladder, bladder distance from point A which is can deliver dose percentage lower about 80% is more than 41 mm.Keywords: Dose sentration, bladder distance, dose distribution.